(untitled) (International Current Pharmaceutical Journal, 2013)
The present study was aimed to investigate antioxidant, analgesic and cytotoxic activity of the methanolic extract of Terminalia chebula Retz. fruits. Antioxidant potential of the extract was evaluated by using nitric oxide scavenging assay, reducing power and total antioxidant capacity. The extract showed significant activities in all antioxidant assays compared to ascorbic acid in a dose dependent mode. In nitric oxide scavenging assay, the IC50 value of the extract was found to be 51.3 µg/mL while the IC50 value of ascorbic acid was 77.4 µg/mL. In addition to strong reducing power, total antioxidant activity of the extract was also found to increase in a dose dependent manner. The analgesic activity was evaluated using acetic acid-induced writhing test in mice. The extract, at a dose of 500 mg/kg, showed a maximum of 44.17 % inhibition (p < 0.05) of writhing reaction compared to the reference drug diclofenac-sodium (66.96 %). The extract also showed moderate cytotoxic activity in brine shrimp lethality bioassay and the LC50 value was found to be 97.36 µg/mL. DOI: http://dx.doi.org/10.3329/icpj.v3i1.17296 International Current Pharmaceutical Journal, December 2013, 3(1): 219-222